Social Exclusion and Land Administration in Orissa, India - Mearns, Robin (The World Bank, 1999)
May 1999 - Which factors prevent the rural poor and other socially excluded groups from having access to land in Orissa, India? The authors report on the first empirical study of its kind to examine - from the perspective of transaction costs - factors that constrain access to land for the rural poor and other socially excluded groups in India. They find that: -Land reform has reduced large landholdings since the 1950s. Medium size farms have gained most. Formidable obstacles still prevent the poor from gaining access to land. -The complexity of land revenue administration in Orissa is partly the legacy of distinctly different systems, which produced more or less complete and accurate land records. These not-so-distant historical records can be important in resolving contemporary land disputes. -Orissa tried legally to abolish land-leasing. Concealed tenancy persisted, with tenants having little protection under the law. -Women's access to and control over land, and their bargaining power with their husbands about land, may be enhanced through joint land titling, a principle yet to be realized in Orissa. -Land administration is viewed as a burden on the state rather than a service, and land records and registration systems are not coordinated. Doing so will improve rights for the poor and reduce transaction costs - but only if the system is transparent and the powerful do not retain the leverage over settlement officers that has allowed land grabs. Land in Orissa may be purchased, inherited, rented (leased), or - in the case of public land and the commons - encroached upon. Each type of transaction - and the State's response, through land law and administration - has implications for poor people's access to land. The authors find that: -Land markets are thin and transaction costs are high, limiting the amount of agricultural land that changes hands.